THE USE OF TRANSCRANIAL MAGNETIC STIMULATION OF THE PREFRONTAL CORTEX IN OCCUPATIONAL POLYNEUROPATHIES - Мартынов, Илья Дмитриевич; Ямщикова, Анастасия Валерьевна; Флейшман, Арнольд Наумович; Петровский, Станислав Альфредович (Medicine in Kuzbass, 2022)
In occupational polyneuropathies, in addition to increasing sympathetic tone and vasospasm, autonomous regulation at the level of suprasegmental autonomic centers is disrupted; the adaptive capabilities of the body might decrease. The aim of the research was studying the clinical effects of transcranial magnetic stimulation of the prefrontal cortex in patients with occupational polyneuropathies. Material and methods. 18 workers of coal mining enterprises with occupational polyneuropathy were examined, the average age was 52.7 ± 2.4 years, and the average work experience was 21.5 ± 4.6 years. In order to determine the severity of the disorders, the parameters of sensory conduction along the nerves of the upper extremities were studied using electroneuromyography. The autonomic regulation was evaluated by spectral analysis of heart rate variability. The functional state of the brain was determined by quantitative evaluation of electroencephalogram signals. Transcranial magnetic stimulation of the prefrontal cortex was performed with individual selection of the stimulation intensity for 3 minutes, the course included 5 procedures. Results. Initially, all examined individuals with occupational polyneuropathy had a decrease in the somatic sensory nerve conduction velocity of the upper extremities, as well as depression of heart rate variability in all frequency ranges. After a course of transcranial magnetic stimulation of the prefrontal cortex, an increase in the average somatic nerve conduction velocity, an increase in spectral parameters of heart rate variability were observed. An increase in the alpha rhythm index reflects an increase in the integrative activity of the brain. There were no stable regional changes in bioelectric activity. Conclusion. Transcranial magnetic stimulation of the prefrontal cortex is effective in correcting sensory and autonomic disorders in occupational polyneuropathies due to the activation of suprasegmental autonomic centers involved in systemic adaptation processes.